(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2013)
An on-farm experiment was undertaken in nine earthen ponds to evaluate the growth and production potentials of stinging catfish shing, Heteropneustes fossilis for the period of six months from March to August 2010. Three stocking densities such as 1,25,000 (T1), 1,87,500 (T2) and 2,50,000 ha-1 (T3) were tested with three replications each. Fish were fed with commercial pelleted feed containing 35% crude protein. After six months rearing, the mean harvesting weights of shing were 69.42±6.20, 58.74±3.85 and 49.50±4.52g in T1, T2 and T3, respectively. Significant (P<0.05) highest mean harvesting weight was found in T1. The best survival was found in T1 (87%) among the treatments. The calculated mean production of shing (H. fossilis) in three treatments such as T1, T2 and T3 were 7549±52, 9031±71 and 8786±60 kg ha-1, respectively, which were significantly different (p<0.05) from each other. DOI: http://dx.doi.org/10.3329/ijarit.v2i2.14009 Int. J. Agril. Res. Innov. & Tech. 2 (2): 9-14 December, 2012